2022
DOI: 10.1126/sciadv.abq1781
|View full text |Cite
|
Sign up to set email alerts
|

Momentum-matching and band-alignment van der Waals heterostructures for high-efficiency infrared photodetection

Abstract: Two-dimensional (2D) infrared photodetectors always suffer from low quantum efficiency (QE) because of the limited atomically thin absorption. Here, we reported 2D black phosphorus (BP)/Bi 2 O 2 Se van der Waals (vdW) photodetectors with momentum-matching and band-alignment heterostructures to achieve high QE. The QE was largely improved by optimizing the generation, suppressing the recombination, and improving the collection of photocarriers. Note that momentum-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 79 publications
6
38
0
Order By: Relevance
“…Most of the 2D materials in few-layered or multilayered structures integrated with Bi 2 O 2 Se always feature an indirect bandgap, suffering from relatively weak light–matter interaction. Although BP is a direct bandgap 2D material that is independent of the number of layers and the vdWs heterojunctions based on Bi 2 O 2 Se/BP possess high photodetection performance, , the intrinsic instability of BP hinders its wide application. , Additionally, monolayer 2D materials such as WS 2 and MoS 2 with direct bandgap show a relatively low light absorption coefficient and low responsivity. The multilayered β-InSe nanoflake (>6 nm) with the merits of tunable electronic properties, broadband photoresponse, and a high light absorption coefficient has a direct bandgap ∼1.25 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the 2D materials in few-layered or multilayered structures integrated with Bi 2 O 2 Se always feature an indirect bandgap, suffering from relatively weak light–matter interaction. Although BP is a direct bandgap 2D material that is independent of the number of layers and the vdWs heterojunctions based on Bi 2 O 2 Se/BP possess high photodetection performance, , the intrinsic instability of BP hinders its wide application. , Additionally, monolayer 2D materials such as WS 2 and MoS 2 with direct bandgap show a relatively low light absorption coefficient and low responsivity. The multilayered β-InSe nanoflake (>6 nm) with the merits of tunable electronic properties, broadband photoresponse, and a high light absorption coefficient has a direct bandgap ∼1.25 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Zhai et al reported a p-WSe 2 /n-Bi 2 O 2 Se vdWs heterojunction photodiode, achieving an ultrahigh rectification ratio of 10 5 attributed to a large band offset. 38 Although BP is a direct bandgap 2D material that is independent of the number of layers and the vdWs heterojunctions based on Bi 2 O 2 Se/BP possess high photodetection performance, 34,44 the intrinsic instability of BP hinders its wide application. 45,46 Additionally, monolayer 2D materials such as WS 2 and MoS 2 with direct bandgap show a relatively low light absorption coefficient and low responsivity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Kwak et al proposed a BP/WS 2 vdWH, which exhibits a high current rectification and solar efficiency because the vdWH may generate a few trap sites in the interface between WS 2 and BP . Chen et al fabricated a 2D BP/Bi 2 O 2 Se vdWH, which can exhibit a high quantum efficiency due to the formed momentum-matching vdWH . The momentum-matching vdWH can support interlayer transitions that are direct in the k-space irrespective of direct or indirect band gap semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…27 Chen et al fabricated a 2D BP/Bi 2 O 2 Se vdWH, which can exhibit a high quantum efficiency due to the formed momentum-matching vdWH. 34 The momentum-matching vdWH can support interlayer transitions that are direct in the k-space irrespective of direct or indirect band gap semiconductors. The momentum-matching vdWH can not only improve the generation rate of photocarriers but also reduce the carrier interface recombination with low latticemismatching scattering and defect-free impurities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the devices mentioned above are limited by the anisotropic absorption of the materials’ internal structure, and required an external electric bias as a driving force to separate the photogenerated carriers. Self-powered photodetectors such as p–n junctions and Schottky barriers are gaining traction for sustainability and energy saving, , with recent studies of self-powered BP/Bi 2 O 2 Se, CNT/Si, and graphene/Si photodetectors demonstrating satisfactory performance. Nonetheless, these detectors suffer from relatively complex fabrication and interface engineering.…”
mentioning
confidence: 99%